CoQ10 augments candesartan protective effect against tourniquet-induced hind limb ischemia-reperfusion: Involvement of non-classical RAS and ROS pathways - Azza S. Awad; Mahmoud Nour El-Din; Rehab Kamel (Elsevier, 2021)
Tourniquet is a well-established model of hind limb ischemia-reperfusion (HLI/R) in rats. Nevertheless, measures should be taken to alleviate the expected injury from ischemia/ reperfusion (I/R). In the present study, 30 adult male Sprague-Dawley rats were randomly divided into 5 groups (n = 6): control, HLI/R, HLI/R given candesartan (1 mg/kg, P.O); HLI/R given Coenzyme Q10 (CoQ10) (10 mg/kg, P.O); HLI/R given candesartan (0.5 mg/kg) and CoQ10 (5 mg/kg). The drugs were administered for 7 days starting one hour after reperfusion. Candesartan and CoQ10 as well as their combination suppressed gastrocnemius content of angiotensin II while they raised angiotensin-converting enzyme 2 (ACE2) activity, angiotensin (1-7) expression, and Mas receptor mRNA level. Consequently, candesartan and/or CoQ10 reversed the oxidative stress and inflammatory changes that occurred following HLI/R as demonstrated by the rise of SOD activity and the decline of MDA, TNF-α, and IL-6 skeletal muscle content. Additionally, candesartan and/or CoQ10 diminished gastrocnemius active caspase-3 level and phospho-p38 MAPK protein expression. Our study proved that CoQ10 enhanced the beneficial effect of candesartan in a model of tourniquet-induced HLI/R by affecting classical and non-classical renin-angiotensin system (RAS) pathway. To our knowledge, this is the first study showing the impact of CoQ10 on skeletal muscle RAS in rats.